The Escola da Terra Program and teacher formation at UFRRJ - Ramofly Bicalho; Pedro Clei Sanches Macedo; Suelen Pereira Estevam (Universidade Federal do Norte do Tocantins, 2022)
The main objective of this article is to present some reflections on the challenges of teacher education in the Escola da Terra Program, considering the pedagogical experiences developed at UFRRJ - Federal Rural University of Rio de Janeiro, in the interface with public policies for rural education. We developed a bibliographical and documentary research, using among the research sources, legislation, ordinances and decrees, as well as theoretical references on rural education and the Escola da Terra Program. We conclude that the collective production of knowledge, in partnership with course participants, teaching staff, tutors, communities and social movements fighting for land, contributed to the appreciation of the stories, memories, desires and identity recognition of the individuals, individual and collective, of the field, in its close relationship with rural schools. We found that this articulation is one of the main challenges to be faced by the rural education movement in Brazil.